2001
DOI: 10.1192/apt.7.6.433
|View full text |Cite
|
Sign up to set email alerts
|

Delirium: the role of psychiatry

Abstract: Acute mental disturbance associated with physical illness is well described in early medical literature, but it was not until 1 AD that Celsus coined the term ‘delirium’ (Lindesay, 1999). Although delirium has many synonyms that are applied in particular clinical settings (Box 1), all acute disturbances of global cognitive functioning are now recognised as ‘delirium’, a consensus supported by both ICD–10 (World Health Organization, 1992) and DSM–IV (American Psychiatric Association, 1994) classification system… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 31 publications
1
11
0
Order By: Relevance
“…In 2006, audits of 1209 hospitalised patients at a teaching hospital in Western Australia identified that approximately 11% of patients had behavioural and cognitive changes suggestive of delirium but only four percent of these patients had a diagnosis of delirium in their medical record (Speed et al, 2007). This finding is consistent with international literature which suggests that delirium often goes unrecognised, undiagnosed and untreated in the hospitalised population (Hustey et al, 2003;Meagher, 1998). It is estimated that the rate of delirium in hospitalised patients ranges from 3.6% in the general population to 89% in high risk groups (Lyketsos et al, 2000;Fick et al, 2002), with most commonly reported incidence rates around 9.4% (Lynch et al, 1998).…”
Section: Introductionsupporting
confidence: 90%
“…In 2006, audits of 1209 hospitalised patients at a teaching hospital in Western Australia identified that approximately 11% of patients had behavioural and cognitive changes suggestive of delirium but only four percent of these patients had a diagnosis of delirium in their medical record (Speed et al, 2007). This finding is consistent with international literature which suggests that delirium often goes unrecognised, undiagnosed and untreated in the hospitalised population (Hustey et al, 2003;Meagher, 1998). It is estimated that the rate of delirium in hospitalised patients ranges from 3.6% in the general population to 89% in high risk groups (Lyketsos et al, 2000;Fick et al, 2002), with most commonly reported incidence rates around 9.4% (Lynch et al, 1998).…”
Section: Introductionsupporting
confidence: 90%
“…In the Western populations it affects between 9 to 30 out of every 100 patients admitted to general hospitals and 16 out of every 100 attenders in elderly accident and emergency. [5][6][7][8] Despite being of public health importance delirium is under diagnosed or misdiagnosed, cases often being construed as mental illness or being given no diagnosis. [5,7,9] There have been relatively few studies clarifying the importance of delirium in sub Saharan Africa in spite of it's public health importance.…”
Section: Introductionmentioning
confidence: 99%
“…; Meagher, 2001). Table 1 lists the various clinical features encountered in the two kinds of delirium and also the commonly corresponding indicators (Granberg, Engberg, & Lundberg, 1996).…”
Section: Clinical Featuresmentioning
confidence: 99%